Pakistan at 100 : Shaping the Future - World Bank (World Bank, Washington, DC, 2019)
Pakistan has several difficult decisions to make. Despite a challenging start and a complex political history, Pakistan's economy grew fast in its earlier years, improving the lives of its citizens. Pakistan was considered an example of successful development in its first 30 years. This has since changed, and Pakistan is struggling to keep pace with the growth and transformation of its peers. Improvements in development outcomes have become slow and uneven. Pakistan@100 seeks to identify the main changes that will be necessary if Pakistan is to become a strong upper middle-income country by the time it turns 100 years old in 2047. The decisions over the next decade will determine Pakistan's future. Will Pakistan rise to the challenges ahead and transform its economy? Or will Pakistan continue with the mixed record of reform implementation, failing to address the key constraints to growth, while another generation of Pakistanis sees limited welfare improvements? This overview report together with the seven policy notes that were prepared in parallel provides a vision of the type of economy that Pakistan could have by 2047. The report illustrates the type of changes that are possible, and it discusses a limited number of priority reforms that will be necessary to address the most pressing constraints to accelerating and sustaining growth.